Assessment of Comprehensive Open Source Library Management Software: Comparative Analysis of phpMyLibrary and Koha - Zahrasadat Hoseini Koushki; Asefeh Asemi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2010)
Open source softwares are those which permit execution, copy, read, distribution, and improvement of the software without any restrictions. Also, automatic library systems can manage library functions. Commercial library sofwares are very expensive. Therefore, open source softwares can be appropriate alternatives for automatic library systems. In addition to providing the general concept of source code softwares, this paper attempts to introduce the most extensively used library open source software packages, including PhpMyLibrary and Koha, and perform a concise comparison with previous studies. Findings of our research indicate that Koha possesses more facilities and in comparison, PhpMyLibrary is not of as much comprehensiveness.